2022
DOI: 10.3332/ecancer.2022.1406
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of total neoadjuvant therapy with 5 × 5 Gy radiation therapy versus conventional chemoradiotherapy for locally advanced rectal cancer among Peruvians

Abstract: Background and Objectives Conventional long-course radiotherapy (LCRT) and a new paradigm of short-course radiotherapy with total neoadjuvant therapy (SCRT-TNT) are used in locally advanced rectal cancer (RC). There are few economic assessment reports available on TNT that focus on cost analysis in a country with limited funding for healthcare systems. The objective of this study was to perform a cost analysis comparing SCRT-TNT versus LCRT. Materials and Methods In 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The positive correlation between the time to start radiotherapy and the distance of origin is probably caused by the patients who live outside the city of Concepción, since they must first anticipate if they move to the province of Concepción or assume the expenses of daily transportation, which generates a delay in their start of treatment. This can be improved if radiotherapy schedules with fewer days of treatment are chosen, clinically tested by clinical trials 11 , which are equivalent to the conventional schedule, and thus reduce radiotherapy weeks 12 , and therefore the expenses related to patient transfer and to public health system 13 . On the other hand, Barrington found that overall survival of patients who live more than 160 km away from the comprehensive cancer center was poorer 14 , with this observation being consistent with findings in our sample, where it can be observed that from 200 km of distance and further, the time to start treatment is markedly prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between the time to start radiotherapy and the distance of origin is probably caused by the patients who live outside the city of Concepción, since they must first anticipate if they move to the province of Concepción or assume the expenses of daily transportation, which generates a delay in their start of treatment. This can be improved if radiotherapy schedules with fewer days of treatment are chosen, clinically tested by clinical trials 11 , which are equivalent to the conventional schedule, and thus reduce radiotherapy weeks 12 , and therefore the expenses related to patient transfer and to public health system 13 . On the other hand, Barrington found that overall survival of patients who live more than 160 km away from the comprehensive cancer center was poorer 14 , with this observation being consistent with findings in our sample, where it can be observed that from 200 km of distance and further, the time to start treatment is markedly prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…For CTRT and HDRBT, the hospital covers the cost of medication; associated supplies, equipment and infrastructure; and the work of healthcare professionals. However, finance and equipment are less than the demand, so it is pertinent to make managerial decisions, supported by efficiency and in addition to the associated costs, as this will allow more cancer treatments to be offered [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the option exists to reduce the number of BATD sessions [ 46 ] but at the teletherapy level, it is not recommended to use hypofractionation in order to reduce the number of sessions as in other pathologies [ 8 , 17 ]. However, the future option exists to offer hypofractionation of 15 sessions followed by 4 BATD applications in women with CT contraindications such as advanced illness with secondary renal dysfunction and hydronephrosis related to the tumour, borderline cardiac function; and fragile patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that advantages should be taken of hypo-fractionated regimens that are just as or more effective than conventional ones. There are many studies that show the benefits of hypo-fractionation in lung cancer [ 22 ], prostate cancer [ 23 ], breast cancer [ 24 ], advanced head cancer [ 25 ], inoperable locally advanced oesophageal cancer [ 26 ] and rectal cancer [ 27 , 28 ], it being as effective as conventional radiotherapy.…”
Section: Discussionmentioning
confidence: 99%